Examining the Views of Physical Education Teachers on Value Expectations in Physical Education and Sports Activities - Ahmet DEVECİ; Mehtap YILDIZ (ümit doğan üstün, 2022)
The purpose of the research was to examine the views of physical education teachers on value expectations in physical education and sports activities. The study was designed as a qualitative research and interview method was used in the research. The research group consisted of 21 physical education teachers (13 Male, 8 Female) who were selected according to the convenient sampling method in 2019-2020 Academic Year in Hatay province. Research data were collected through a semi-structured interview form developed by the researchers. In the research, the data were evaluated by content analysis method. According to the results of the research, it was determined that most of the physical education teachers expected their students to exhibit behaviors towards sportive virtue in cases of winning and losing, and some others expected their students to always be on the winning side. Besides, it was determined that physical education teachers stated that moral values were more important in sports tournaments held between schools and provinces, and that both material and moral values were an inseparable whole.